2019
DOI: 10.1051/0004-6361/201935532
|View full text |Cite
|
Sign up to set email alerts
|

The essential elements of dust evolution

Abstract: Context. There remain many open questions relating to the depletion of elements into dust, e.g., exactly how are C and O incorporated into dust in dense clouds and, in particular, what drives the disappearance of oxygen in the denser interstellar medium? Aims. This work is, in part, an attempt to explain the apparently anomalous incorporation of O atoms into dust in dense clouds. Methods. We re-visit the question of the depletion of the elements incorporated into the carbonaceous component of interstellar dust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 104 publications
1
19
0
Order By: Relevance
“…rates (f survival of 37-89%) and low grain growth efficiencies ( of 30-40). These long grain growth timescales could reduce the tension between the high grain growth efficiencies (required to reproduce the large dust masses observed in lowto high-redshift galaxies) and grain surface chemical models, which currently fail to account for efficient grain growth processes in the interstellar medium (e.g., Barlow 1978;Ferrara et al 2016;Ceccarelli et al 2018;Jones & Ysard 2019).…”
Section: Dominant Dust Production Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…rates (f survival of 37-89%) and low grain growth efficiencies ( of 30-40). These long grain growth timescales could reduce the tension between the high grain growth efficiencies (required to reproduce the large dust masses observed in lowto high-redshift galaxies) and grain surface chemical models, which currently fail to account for efficient grain growth processes in the interstellar medium (e.g., Barlow 1978;Ferrara et al 2016;Ceccarelli et al 2018;Jones & Ysard 2019).…”
Section: Dominant Dust Production Sourcesmentioning
confidence: 99%
“…We speculate that these models provide an alternative to earlier work that required vigorous dust destruction and efficient grain growth on timescales a few Myr (e.g., Draine 2009;Zhukovska 2014;Feldmann 2015;De Vis et al 2017b) to explain local galaxy scaling relations. These long dust lifetimes and reduced grain growth efficiencies could reduce the tension with grain-surface chemical models (e.g., Barlow 1978;Ferrara et al 2016;Ceccarelli et al 2018;Jones & Ysard 2019) that have not been able to come up with efficient grain growth mechanisms in interstellar clouds. Our model results might furthermore help solving the dust budget problem at high redshifts (e.g., Bertoldi et al 2003;Priddey et al 2003;Watson et al 2015), in case similar dust production and destruction efficiencies would apply to those primordial galaxies.…”
Section: Binmentioning
confidence: 99%
“…It was shown that the photolysis of carbonates presented in the substrate was possibly a source of CO2, CO, carbon and oxygen atoms. Organic carbonates can form in the translucent ISM before the formation of molecular ices [273].…”
Section: Mennella Et Al Irradiated H2o Ices On Hydrogenated Amorphous...mentioning
confidence: 99%
“…When the molecular clouds are dissociated, the ice mantles evaporate and only ≈ 10 per cent of the cloud dust mass accreted in dense clouds survives as a refractory material in the transition into the diffuse ISM (Jones & Ysard, 2019). We set f dis = 0.1 (Equation 10) to account for this.…”
Section: Dust Parametersmentioning
confidence: 99%